Network regulation and properties optimization of glycidyl azide polymer‐based materials as a candidate of solid propellant binder via alternating the functionality of propargyl‐terminated polyether. Issue 40 (10th June 2019) - Qi, Chun; Tang, Gen; Guo, Xiang; Liu, Changhua; Pang, Ai‐min; Gan, Lin; Huang, Jin
ABSTRACT: A kind of glycidyl azide polymer (GAP)‐based composite has been fabricated using propargyl‐terminated ethylene oxide‐tetrahydrofuran copolymer (PPET) with two ( p‐ ) and three ( t‐ ) alkyne functionalities via Huisgen reaction. Independent upon the PPET functionality, both crosslink densities and mechanical properties for two GAP/PPET systems showed a positive‐interrelation changes of initial increase and subsequent decrease with an increase of azide/alkyne molar ratios. At equivalent of azide/alkyne molar ratios, the composites containing t‐ PPET with higher alkyne functionality exhibited better mechanical properties, while those with two alkyne functionality presented lower glass transition. Under the regulation of alkyne functionality as 3 and azide/alkyne molar ratio as 3:1, the tensile strength, Young's modulus and breaking elongation could simultaneously reach the maximum values of 1.38 MPa, 4.07 MPa, and 122.5%, which was ascribed to optimal participation of azide/alkyne reaction into network construction. Overall, this study provides an additional optimization route for network‐structured binders in solid propellant system. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48016. Abstract : The PPET/GAP crosslinking network control and mechanical adjustment via using crosslinker with different numbers of functional groups.